Advances in neuromodulation for treatment of prolonged disorders of consciousness - HE Chen; SONG Ming; XU Long (Chinese Journal of Contemporary Neurology and Neurosurgery)
Neuromodulation has emerged as a significant clinical treatment modality for patients with prolonged disorders of consciousness (pDOC), encompassing both non⁃invasive and invasive neuromodulation techniques. This paper integrates an overview of the neural mechanisms underlying consciousness, neurofunctional assessments, and categorizes the current applications and recent research findings in non⁃invasive and invasive neuromodulation techniques. The aim is to enhance the scientific rigor and efficacy of neuromodulation, provide robust support for the treatment of pDOC.